Perkembangan Kurikulum IPS SD - Afriliya Nadia Putri; Siti Fatimah; Firli Maulidiana; Ryzca Siti Qomariyah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2022)
This article aims to understand the development of social studies curriculum both in Indonesia and outside the country. General Learning Objectives after studying this subject is that we are expected to be able to analyze the nature of the Social Studies Education curriculum. The method used is reading sources and gathering information so articles, journals and books. The results obtained in writing this article are teachers as agents of curriculum renewal who act as leaders and supporters of values in society and as facilitators in learning.Keywords:curriculum, social studies, teacher, method, development